2014
DOI: 10.1371/journal.pone.0105098
|View full text |Cite
|
Sign up to set email alerts
|

Subtype Classification of Iranian HIV-1 Sequences Registered in the HIV Databases, 2006-2013

Abstract: BackgroundThe rate of human immunodeficiency virus type 1 (HIV-1) infection in Iran has increased dramatically in the past few years. While the earliest cases were among hemophiliacs, injection drug users (IDUs) fuel the current epidemic. Previous molecular epidemiological analysis found that subtype A was most common among IDUs but more recent studies suggest CRF_35AD may be more prevalent now. To gain a better understanding of the molecular epidemiology of HIV-1 infection in Iran, we analyzed all Iranian HIV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
(20 reference statements)
7
15
0
Order By: Relevance
“…Most samples in the study were determined to be infected with the CRF35_AD variant, 96.1%, like other studies [24,25,26,27,28], and there were far fewer cases of subtypes B, AE, and A1 (<1.3%). In Iran, CRF35-AD has an epidemiological connection with CRF35-AD.…”
Section: Discussionsupporting
confidence: 63%
“…Most samples in the study were determined to be infected with the CRF35_AD variant, 96.1%, like other studies [24,25,26,27,28], and there were far fewer cases of subtypes B, AE, and A1 (<1.3%). In Iran, CRF35-AD has an epidemiological connection with CRF35-AD.…”
Section: Discussionsupporting
confidence: 63%
“…In this study, the HIV-1 subtypes CRF01_AE, C, and B were found to be the most prevalent subtypes detected in Kuwait, consistent with previous observations [6] and the findings reported in the Gulf region about the circulation of pure subtypes A, B, and C and of recombinant forms like CRF35_AD [21,22]. Of interest, around 10% of the patients had the HIV-1 subtype CRF02_AG that is prevalent in West Africa and Russia with a global prevalence of ∼5% [23].…”
Section: Discussionsupporting
confidence: 92%
“…The dominant virus subtypes in this study were CRF35-AD (48%) and A1 (43%), followed by C and CPX (4.8%); these findings were observed in previous studies, in which CRF_35AD was indicated as the dominant subtype in Iran [5, 23]. However, our study additionally observed the CPX subtype in two samples for the first time in Iran.…”
Section: Discussionsupporting
confidence: 86%
“…This issue forced the physicians to replace the patients’ drug regimen with second-line medications. This may result in new side effects and immense financial burden on health systems [4, 5]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation